2012
DOI: 10.4149/neo_2013_007
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Shows Partial Oncostatic Effect in Rat Mammary Carcinogenesis

Abstract: Peroral antidiabetics from thiazolidinedione (glitazone) group showed oncostatic effects in preclinical models. This study evaluated chemopreventive effects of rosiglitazone in N-methyl-N-nitrosourea-induced mammary carcinogenesis in rats. N-methyl-N-nitrosourea was administered in two intraperitoneal doses each per 50 mg/kg b.w. between 40 th and 51 st postnatal days. Rosiglitazone was administered in a diet at a concentration of 10 ppm and 100 ppm, respectively, 9 days before the first carcinogen dose until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Differences between the AIN-93G-based diets (casein and ISP diets) and the Teklad 2018-based diets include the levels of vitamin A, vitamin K, several B vitamins (B1, B2, B3, B5, B6, B7, and B9) and the complexity of the carbohydrates. Vitamins B2 (riboflavin), B6 (pyridoxine), and B9 (folate) have been implicated in reducing breast cancer risk (28-30) while higher blood glucose levels associated with simple carbohydrates like those found in the casein and ISP diets have been associated with increased breast cancer risk in humans (31)(32)(33)(34) and rodents (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Differences between the AIN-93G-based diets (casein and ISP diets) and the Teklad 2018-based diets include the levels of vitamin A, vitamin K, several B vitamins (B1, B2, B3, B5, B6, B7, and B9) and the complexity of the carbohydrates. Vitamins B2 (riboflavin), B6 (pyridoxine), and B9 (folate) have been implicated in reducing breast cancer risk (28-30) while higher blood glucose levels associated with simple carbohydrates like those found in the casein and ISP diets have been associated with increased breast cancer risk in humans (31)(32)(33)(34) and rodents (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ activation is regarded as the key mechanism of anticancer effects of glitazones. PPARγ agonists, in most cases, inhibited proliferation and growth of experimental breast, lung, gastrointestinal, liver, pancreatic, ovarian, testicular and urinary system cancers [292,293,294,295,296]. Antitumor properties independent of PPARγ activation were reported too, including the regulation of differentiation, inflammation and apoptosis; however, it is not always possible to determine whether an effect that is independent of PPARγ-regulated transcriptional control is also independent of the presence of PPARγ protein [297,298].…”
Section: Pleiotropic Drugs and Mel In Cancer Prevention/treatmentmentioning
confidence: 99%
“…It is involved in the regulation of carbohydrate metabolism and adipogenesis in cells and also participates in the inflammatory response as well as the differentiation and apoptosis of tumor cells [ 15 ]. Researchers has found that after being activated by ligand, PPAR γ can induce tumor cell differentiation, repress their proliferation, promote their apoptosis, and concomitantly reduce neoplastic angiogenesis, which eventually halts the tumor growth, proliferation, infiltration, and metastasis [ 16 , 17 ]. Its most important function is mediation of gene transcription and subsequent regulation on its activation after combining with its ligands.…”
Section: Function Of Ppar γmentioning
confidence: 99%